THE MEANING COMPONENTS OF THE WORD “DRINKING” IN JAVANESE LANGUAGE - Sigit Yulianto; Widhyasmaramurti (ADISAM Publisher, 2024)
In the second edition of the Kamus Basa Jawa Bausastra Jawa (KBJ (BJ) 2), published in 2011, 19 words meaning 'drinking' were found. The nineteen words meaning 'drinking' have simple definitions and must be more detailed. The meaning components used as elements in defining words have also not been fully explained. This can lead to inaccurate use of the word drinking. Therefore, this research discusses the component analysis of the meaning of the word drinking in Javanese using the KBJ (BJ) 2 dictionary as a data source. The aim of this research is to describe the components of the meaning of the word drinking in Javanese in KBJ (BJ) 2. This research method is a qualitative descriptive method with a lexical semantic approach. Using Nida's (1975) theory, the research results show that there is 1 main meaning component, 4 differentiating meaning components, and 28 complementary meaning components. These meaning components can be added and arranged to complete the definition of the word drinking in the Javanese monolingual dictionary next after KBJ (BJ) 2. The definition of the word drinking in KBJ (BJ) 2 does not yet explain the meaning components related to the perpetrator of the act of drinking, the object being drunk, the position of the mouth and lips when drinking, the device used, and how to do it.